APPLICATION OF HIGH-ORDER SPECTRA AND COHERENCE FOR ANALYZING NONLINEARITY OF A GROUND RESPONSE - Pavlenko O.V. (My University, 2006)
It is known that high-order spectra (second order) and coherences (greater than two) are used to detect phase-correlated oscillations in stationary time series. High-order coherences (HOCs) serve as a measure of phase relations [1]. HOC functions are determined as high-order spectra (HOS) normalized by power spectra. The HOCs (mainly, bicoherence) are more frequently used in practical applications: estimates of bicoherence obtained for time series are compared with expected mean values for the case when the true value of bicoherence is zero (for example, for Gaussian noise).